Lightweight aggregate for household garbage incineration ash-fly ash-slag road as well as preparation and application of lightweight aggregate
By incineration of domestic waste, such as ash, fly ash and slag, the problem of low utilization of fly ash and slag is solved, efficient resource utilization is achieved, the performance of aggregates is improved, carbon emissions are reduced, and environmental protection and resource recycling are promoted.
Patent Information
- Application Number
- CN202510063157.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
The existing technology is difficult to effectively utilize domestic waste incineration ash, especially fly ash, due to its dangerous nature, and the utilization of slag in some areas is limited by heavy metal leaching problems, resulting in a low comprehensive utilization rate. At the same time, the demand for sand and gravel materials in road construction is growing.
Lightweight aggregates for the way out are prepared by resource utilization of waste such as incineration of domestic waste (including fly ash and furnace slag), fly ash and slag. This aggregate uses a ground polymer instead of traditional cement cementitious materials, and uses slag to replace fine aggregates, and combines the synergistic effect of fly ash and slag to form an aggregate with high compressive strength and low heavy metal leaching concentration.
It has achieved efficient and comprehensive utilization of domestic waste incineration ash, improved the compressive strength and durability of aggregates, reduced carbon emissions, saved cement resources, alleviated the shortage of sand and gravel materials, and promoted environmental protection and resource recycling.
Smart Images

Figure CN119841588A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of highway engineering, and specifically relates to a lightweight aggregate for road prepared by synergistic use of domestic waste incineration ash-fly ash-slag, and the preparation and application thereof. Background Art
[0002] In recent years, the continuous development of urbanization and industrialization has brought great pressure to the human living environment, such as the accumulation of industrial solid waste, pollution and difficulty in harmless treatment caused by the ash produced by domestic waste incineration plants. Realizing its harmless and resource-based multi-dimensional utilization is an important goal at present. At present, incineration is becoming popular to consume the increasing amount of urban domestic waste. Compared with sanitary landfill, incineration of garbage can not only reduce land occupation, but also use the heat generated by incineration to generate electricity. The ash after garbage incineration includes fly ash and slag. Fly ash refers to the residual hazardous waste collected during the garbage incineration process and contains heavy metals, accounting for about 20% of the total mass of ash; fly ash contains harmful substances such as heavy metals and is a hazardous waste. It needs to be solidified before landfill. The existing technology usually uses solidification / stabilization methods to treat fly ash, such as cement solidification, lime solidification, etc. Although it can effectively reduce the leaching rate of heavy metals in fly ash, the treatment cost is high, and the solidified product is difficult to reuse, thus limiting its resource utilization. Slag refers to the product left on the furnace bed, accounting for about 80% of the ash mass. It has good physical and chemical properties and low heavy metal content. It is mainly composed of slag, black and non-ferrous metals, ceramic fragments and other substances. The heavy metal content is not high, but direct use still faces problems such as heavy metal leaching. Slag is a general solid waste. After wet treatment, impurities are removed and metal substances are recycled. The resulting product is called tailings; tailings can be used for roadbed filling after crushing, grading, and adjusting particle size, but it is limited by the concentration of heavy metal leaching and is not suitable for areas with abundant groundwater and heavy rain.
[0003] Despite the above treatment methods, the comprehensive utilization rate of fly ash and slag is still low due to the characteristics of fly ash and slag, especially fly ash is difficult to be widely used due to its hazardous nature. With the rapid development of road construction, the demand for sand and gravel materials has surged, and traditional sand and gravel resources are becoming increasingly scarce, so alternative materials need to be found. Domestic and foreign scholars are studying the use of industrial waste (such as fly ash, slag, etc.) to prepare alternative sand and gravel materials. Although these materials have certain performance advantages, the preparation process is complex and the cost is high. Use geopolymers to treat fly ash. By using fly ash as the main raw material and adding active silicon-aluminum active substances to prepare geopolymers under alkali excitation to replace traditional cement, geopolymers can generate three-dimensional network-like zeolite cage-like stereoscopic structures to solidify heavy metal ions in the structure; using MSWI mixed with cement-stabilized crushed stone base is an effective way to realize MSWI resource utilization, but due to the low strength and high water absorption of MSWI, the utilization rate is greatly limited, so the comprehensive utilization rate of ash and slag is still low. In order to be able to more efficiently utilize the domestic waste incineration ash, many scholars have deeply developed its application scenarios based on existing research. They have used geopolymers prepared by MFA and MSWI to prepare lightweight aggregates for roads. On the basis of geopolymers, they have further developed the application of MFA, which has improved the comprehensive utilization efficiency of domestic waste incineration ash. According to statistics, for every ton of ordinary Portland cement produced, about 616.6 kg of CO2 is emitted, and for every ton of lightweight aggregates produced for roads, 0.1 tons of cement will be saved, 0.7 tons of domestic waste incineration ash will be consumed, and CO2 emissions will be reduced by about 65 kg. This can not only alleviate the shortage of sand and gravel materials, but also reduce pollution and protect the environment.
[0004] In summary, traditional fly ash treatment methods have disadvantages such as high cost and difficulty in reusing solidified products. Slag treatment methods are only used in the low-end market, and their high value-added utilization potential has not been fully explored. The demand for sand and gravel materials in road construction is growing, and traditional sand and gravel resources are becoming increasingly scarce. Finding alternative materials has become an industry consensus. Industrial waste such as fly ash and slag has been widely studied for the preparation of building materials because of its certain active ingredients, but it is often difficult to meet high performance requirements when used alone. Summary of the invention
[0005] In view of the current difficulties in handling the ash and slag from the incineration of domestic waste brought about by the rapid development of urbanization and industrialization, especially the harmless treatment and resource utilization of fly ash and slag, as well as the technical status quo of the shortage of sand and gravel materials for road construction, the present invention aims to provide a lightweight aggregate for roads made of domestic waste incineration ash and slag, and its preparation and application, using fly ash to prepare geopolymers to replace traditional cement cementitious materials, while using slag to replace fine aggregates, and combining the synergistic effect of fly ash and slag to prepare lightweight aggregates for roads. The aggregate not only has high compressive strength and low heavy metal leaching concentration, and has little impact on the environment, but also has strength that meets the requirements of lightweight aggregate specifications, effectively improving the comprehensive utilization efficiency of domestic waste incineration ash and slag. In addition, the production of the aggregate can also save cement, reduce CO2 emissions, alleviate the shortage of sand and gravel materials, and achieve the dual goals of environmental protection and resource recycling.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention provides a road lightweight aggregate of domestic waste incineration ash-fly ash-slag. Calculated by mass percentage, the road lightweight aggregate comprises 8-15% of domestic waste incineration fly ash, 4-8% of fly ash, 29-41% of slag powder, 14-31% of domestic waste incineration furnace slag, 3-5% of alkali activator and 21-24% of distilled water.
[0007] The bulk density of the lightweight aggregate for road use is 1000-1200 kg / m³, the cylinder compressive strength after 28 days is 6-11 MPa, the water absorption rate is 8-10%, and the particle size is 8-10 mm.
[0008] The slag is the product remaining on the roadbed from the incineration of domestic waste, and its CaO mass percentage content is 29.94%, and SiO2 mass percentage content is 34.35%; the mass percentage contents of SiO2 and Al2O3 in the fly ash are 51.72% and 43.33% respectively; the mass percentage contents of SiO2 and Al2O3 in the slag powder are 22.97% and 24.57% respectively.
[0009] The present invention provides a method for preparing the above-mentioned road lightweight aggregate of domestic waste incineration ash-fly ash-slag, comprising: S1, weighing sodium silicate and sodium hydroxide, dissolving them in distilled water, and aging them to obtain an alkaline activator; S2, mix the weighed fly ash, fly ash and slag powder evenly, add the alkali activator obtained in S1, stir slowly and quickly to obtain a low polymer slurry; S3, weighing slag and slag powder and adding them to the geopolymer slurry obtained in S2, continuously and evenly adding the calculated remaining water, stirring and granulating, screening, and curing to obtain lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag.
[0010] The mass ratio of the sodium silicate to the sodium hydroxide is 1:2-3.
[0011] Furthermore, the mass ratio of the sodium silicate to the sodium hydroxide is 1:2.72.
[0012] Furthermore, the purity of the sodium hydroxide is ≥90%; the sodium silicate is instant powdered sodium silicate; the dissolution rate of the sodium silicate is ≤240s (30°C); and the 120-mesh screening rate of the sodium silicate is ≥95%.
[0013] The aging is performed by standing the mixture in a closed environment at room temperature for 1 to 4 hours.
[0014] Furthermore, the aging time is 4 hours.
[0015] The mass ratio of the fly ash, fly ash and slag powder is 2:1:2.
[0016] The mass ratio of the geopolymer slurry to the base material (slag powder+slag) is 3:7-5:5.
[0017] The slow stirring time is 60s, the fast stirring time is 180s, the slow stirring speed is 140±5r / min, and the fast stirring speed is 285±10r / min.
[0018] The above-mentioned road lightweight aggregate of domestic waste incineration ash-fly ash-slag is used in road base, preparation of non-structural concrete such as curbstones and road cushions.
[0019] The lightweight road aggregate with a 28 d cylinder compressive strength of less than 7 MPa is low-grade lightweight road aggregate, and greater than 7 MPa is high-grade lightweight road aggregate. The low-grade lightweight road aggregate is used for road cushions, and the high-grade lightweight road aggregate is used for road bases or for preparing non-structural concrete such as curbstones.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The domestic waste incineration ash-fly ash-slag road lightweight aggregate provided by the present invention realizes the effective treatment and reuse of waste by resource utilization of domestic waste incineration ash (including fly ash and slag), fly ash and slag, etc., and converting them into road lightweight aggregate. The lightweight aggregate has the following characteristics: 1) Lightweight and high strength: The bulk density of the lightweight aggregate is moderate (1000-1200 kg / m³), and the cylinder pressure strength after 28 days reaches 6-11 MPa, which not only meets the lightweight requirements, but also has a certain strength, and is suitable for the construction needs of different grades of roads; 2) Moderate water absorption: The water absorption rate is controlled at 8-10%, which is beneficial to the stability and durability of the aggregate in concrete; 3) Uniform particle size: The particle size is 8-10 mm, which ensures the uniform distribution of the aggregate in the concrete and good working performance. Compared with the road lightweight aggregate prepared by ordinary Portland cement, the present invention uses solid waste-based cementitious materials instead of cement, which significantly reduces carbon emissions. The preparation of 1 ton of lightweight aggregate for road use can save about 0.1 ton of cement, while absorbing 0.7 ton of ash from the incineration of domestic waste and reducing CO2 emissions by about 65 kg. This is not only conducive to coping with global climate change, but also promotes the recycling of resources.
[0021] The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag provided by the present invention makes full use of various industrial wastes such as domestic waste incineration ash (including fly ash MFA and slag MSWI), fly ash and slag, and realizes effective integration and recycling of resources; the use of alkali activator significantly improves the chemical reaction activity between raw materials, promotes the formation of network structure, and thus improves the strength and durability of aggregates; through the excitation of alkali activator, a geopolymer slurry with high strength and durability is formed. This provides a solid foundation for subsequent granulation and the performance of the final product.
[0022] Furthermore, by dissolving and aging sodium silicate and sodium hydroxide, an alkali activator is prepared, which can effectively activate the activity of fly ash and slag powder and improve the performance of aggregates; the combination of slow stirring and fast stirring ensures the full mixing and uniform distribution of raw materials, which is conducive to the stability and uniformity of aggregate quality; adding an appropriate amount of water during the stirring process helps to form a uniform low-polymer slurry, which provides a good foundation for subsequent granulation and screening; by continuously and evenly adding the remaining water and stirring and granulating, a lightweight aggregate for road use with uniform particle size and stable performance is finally obtained, and the appropriate curing process helps to further improve the strength of the aggregate and stabilize the performance. By reasonable curing time and condition control, it can be ensured that the aggregate has good durability and stability in practical applications.
[0023] The application provided by the present invention is that the lightweight aggregate is suitable for multiple fields such as road base, preparation of non-structural concrete such as curbstones and road cushions, and has broad application prospects. According to the 28-day cylinder compressive strength of the aggregate, it is divided into low-grade and high-grade categories, which are respectively suitable for different road construction needs, thereby achieving rational utilization and performance optimization of the aggregate. It promotes technological innovation and industrial upgrading in the field of solid waste resource utilization. It demonstrates the feasibility of converting traditional waste into high-performance building materials, and provides useful reference and inspiration for other solid waste resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A preparation flow chart for the synergistic preparation of road lightweight aggregates from domestic waste incineration ash-fly ash-slag; Figure 2 A physical picture shows the coordinated preparation of lightweight aggregate for road use using domestic waste incineration ash, fly ash and slag. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 Weighing: According to the mass percentages of MFA, fly ash, slag powder, sodium hydroxide, sodium silicate and distilled water being 9.1%, 4.5%, 9.1%, 0.8% and 2.3% respectively and the water-cement ratio being 0.5, weigh 120g of fly ash, 60g of fly ash, 120g of slag powder, 11g of flaky sodium hydroxide, 30g of instant powdered sodium silicate and 150g of distilled water respectively.
[0027] Preparation of alkali activator: Calculate that the total water is 280g, the water for alkali activator is 150g, and the water added to the granulation is 130g. Then pour the water for alkali activator into a beaker and place it on a magnetic stirrer to heat it to about 40°C. Weigh the sodium silicate and sodium hydroxide calculated according to the specified modulus. First, slowly pour the sodium silicate into the beaker in 3-5 times and stir it continuously with a magnetic stirrer. After the sodium silicate is completely dissolved, pour the sodium hydroxide into distilled water in 3 times until most of the particles are dissolved. Adjust the magnetic stirrer to room temperature and continue stirring for 15 minutes until the solution color becomes transparent and clear without flocs. Finally, take out the mixed solution that is stirred evenly, seal the cup mouth with a polyethylene film for aging to obtain the alkali activator; in the present invention, the aging time is preferably 1-4h, more preferably 4h. The polyethylene film sealed on the cup mouth of the present invention can prevent water from evaporating and losing.
[0028] (3) Prepare geopolymer slurry: Pour the weighed MFA, fly ash and slag powder into a dry stirring pot, turn on the switch, stir slowly for 1 minute and evenly add the alkali activator. Note that the alkali activator should be added as close to the edge of the fan blade as possible to prevent the alkali activator from adhering to the fan blade. Then stir quickly for 3 minutes until the raw materials are evenly mixed. Then pour the aged alkali activator evenly into the stirring pot, turn on the switch and stir quickly for 1 minute until the geopolymer slurry is fully stirred.
[0029] (4) Preparation of granules: According to the mass percentage of MSWI and slag powder of 21.2% and 31.8%, 280g of slag and 420g of slag powder were weighed and added evenly and slowly to the geopolymer slurry being stirred, and the geopolymer slurry and MSWI were fully mixed until no obvious dry matter appeared. Then, the remaining water of 130g was continuously and evenly added to allow the granules to fully absorb water, and the granules were stirred continuously and quickly until the granules were uniformly and slightly moist. (5) Granulation: Pour the stirred granules into the feed port of the extrusion granulator and gently shake the feed port to make the granules dense. Then start the granulator, and the granules are slowly extruded into spherical shapes and fall into the tray. (6) Curing: The prepared lightweight aggregate for road use was screened and naturally cured for 1 day. It was then packed into sealed bags and placed in a standard curing box for curing. The bulk density, cylinder pressure strength and water absorption rate at 28 days were tested. The test results are shown in Table 1.
[0030] The test methods and test conditions for each item are as follows: (a) Bulk density This test is based on "Light Aggregate and Its Test Method". After drying the lightweight aggregate for road use, use a sampling spoon to pour the sample evenly from 50mm above the container mouth (or use a standard slide bucket), let the sample fall naturally, and do not hit the container. After filling, make the sample on the upper mouth of the container into a cone, then use a ruler to scrape it flat from the center to both sides along the edge of the container, fill the concave parts with aggregates of smaller particle size, and weigh them.
[0031] (b) Cylinder pressure strength This test is based on "Light Aggregate and Its Test Methods". The sample is placed in a pressure cylinder and vibrated to compact. The pressure cylinder is placed on the lower platen of the press, aligned with the center of the platen, and loaded at a uniform speed of 300N~500N per second. When the stamping die is 20mm in diameter, the pressure value is recorded, and then the cylinder pressure strength is calculated. (c) Water absorption This test is based on "Light Aggregate and Its Test Methods". Take a certain mass of sample, soak it in water for 1 hour, absorb the surface moisture with a towel, make the sample saturated and dry, and then weigh it. Calculate according to the formula for coarse aggregate water absorption.
[0032] Table 1: Test results of lightweight aggregate performance in Example 1
[0033] It can be seen from Table 1 that according to the measured bulk density, the density grade is classified into 1100 according to "Light Aggregate and Its Test Method" (GB / T 17431-2010). The cylinder compressive strength of the lightweight aggregate for road use in Example 1 of the present invention at 28 days is 6.5 MPa and the water absorption rate is 9.3%, which meets the technical requirements of not less than 5.0 MPa and not more than 10% under its density grade.
[0034] On the premise of meeting the requirements of the specifications, according to the classification of its cylinder pressure strength grade, Example 1 belongs to a low-grade lightweight aggregate for road use. It is recommended to be used in occasions with low strength requirements such as pavement cushion layers. It has good frost resistance and provides a good working environment for the roadbed.
[0035] Example 2 According to MFA8.9%, fly ash4.5%, slag powder35%, slag26.1%, alkali activator3.1%, and distilled water22.4%, weigh MFA120g, fly ash60g, slag powder470g, slag350g, alkali activator41g, and distilled water300g; the preparation method, test methods for each item, and test conditions are the same as those in Example 1.
[0036] Table 2: Test results of lightweight aggregate performance in Example 2
[0037] It can be seen from Table 1 that according to the measured bulk density, the density grade is classified as 1200 according to "Light Aggregate and Its Test Method" (GB / T 17431-2010). The cylinder compressive strength of the lightweight aggregate for road use in Example 2 of the present invention at 28 days is 10.1 MPa, and the water absorption rate is 8.7%, which meets the technical requirements of GB17431.2-2010 "Light Aggregate and Its Test Method" of not less than 5.0 MPa and not more than 10%.
[0038] On the premise of meeting the requirements of the specifications, according to the classification of its cylinder pressure strength grade, Example 2 belongs to a high-grade lightweight aggregate for road use. It is recommended to be applied to non-structural concrete such as pavement base or curbstones, ensuring high strength while having good durability. Example 3 According to MFA 14.5%, fly ash 7.28%, slag powder 36.4%, slag 14.5%, alkali activator .95%, and distilled water 21.8%, weigh 200g MFA, 100g fly ash, 500g slag powder, 200g slag, 68g alkali activator, and 300g distilled water; the preparation method, test methods for each item, and test conditions are the same as those in Example 1.
[0039] Table 3: Test results of lightweight aggregate performance in Example 3
[0040] It can be seen from Table 3 that according to the measured bulk density, the density grade is classified as 1200 according to "Light Aggregate and Its Test Method" (GB / T 17431-2010). The cylinder compressive strength of the lightweight aggregate for road use in Example 3 of the present invention at 28 days is 7.8 MPa, and the water absorption rate is 9.5%, which meets the technical requirements of GB17431.2-2010 "Light Aggregate and Its Test Method" of not less than 5.0 MPa and not more than 10%.
[0041] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A road lightweight aggregate of domestic waste incineration ash-fly ash-slag, characterized in that: Calculated by mass percentage, the lightweight aggregate for the road includes 8~15% fly ash from incineration of domestic waste, 4~8% fly ash, 29~41% slag powder, 14~31% slag from incineration of domestic waste, 3~5% alkali activator, and 21~24% distilled water.
2. The road lightweight aggregate of domestic waste incineration ash-fly ash-slag according to claim 1 is characterized in that: The bulk density of the lightweight road aggregate is 1000 kg / m³~1200 kg / m³, the 28-day cylinder pressure strength is 6 MPa~11 MPa, the water absorption rate is 8%~10%, and the particle size is 8 mm~10 mm.
3. The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag according to claims 1-2, characterized in that: include: S1, weighing sodium silicate and sodium hydroxide, dissolving them in distilled water, and aging them to obtain an alkaline activator; S2, mix the weighed fly ash, fly ash and slag powder evenly, add the alkali activator obtained in S1, stir slowly and quickly to obtain geopolymer slurry; S3, weighing slag and slag powder and adding them to the geopolymer slurry obtained in S2, continuously and evenly adding the calculated remaining water, stirring and granulating, screening, and curing to obtain lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag.
4. The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag according to claim 3, characterized in that: The mass ratio of the sodium silicate to the sodium hydroxide is 1:2-3.
5. The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag according to claim 3, characterized in that: The aging is performed by standing the mixture in a closed environment at room temperature for 1 to 4 hours.
6. The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag according to claim 3, characterized in that: The mass ratio of the fly ash, fly ash and slag powder is 2:1:
2.
7. The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag according to claim 3, characterized in that: The mass ratio of the geopolymer slurry, slag powder and slag is 3:7-5:
5.
8. The method for preparing lightweight aggregate for road use of domestic waste incineration ash-fly ash-slag according to claim 3, characterized in that: The slow stirring time is 50-70 s, the fast stirring time is 170-190 s, the slow stirring speed is 140±5 r / min, and the fast stirring speed is 285±10 r / min.
9. Use of the road lightweight aggregate of domestic waste incineration ash-fly ash-slag as described in any one of claims 1 to 2 in road base, preparation of non-structural concrete such as curbstones, and road cushions.
10. The use according to claim 9, characterized in that: The lightweight road aggregate with a 28 d cylinder compressive strength of less than 7 MPa is low-grade lightweight road aggregate, and greater than 7 MPa is high-grade lightweight road aggregate. The low-grade lightweight road aggregate is used for road cushions, and the high-grade lightweight road aggregate is used for road bases or for preparing non-structural concrete such as curbstones.